7(2x-1)=3(15-4x)

Simple and best practice solution for 7(2x-1)=3(15-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2x-1)=3(15-4x) equation:


Simplifying
7(2x + -1) = 3(15 + -4x)

Reorder the terms:
7(-1 + 2x) = 3(15 + -4x)
(-1 * 7 + 2x * 7) = 3(15 + -4x)
(-7 + 14x) = 3(15 + -4x)
-7 + 14x = (15 * 3 + -4x * 3)
-7 + 14x = (45 + -12x)

Solving
-7 + 14x = 45 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-7 + 14x + 12x = 45 + -12x + 12x

Combine like terms: 14x + 12x = 26x
-7 + 26x = 45 + -12x + 12x

Combine like terms: -12x + 12x = 0
-7 + 26x = 45 + 0
-7 + 26x = 45

Add '7' to each side of the equation.
-7 + 7 + 26x = 45 + 7

Combine like terms: -7 + 7 = 0
0 + 26x = 45 + 7
26x = 45 + 7

Combine like terms: 45 + 7 = 52
26x = 52

Divide each side by '26'.
x = 2

Simplifying
x = 2

See similar equations:

| 6x^2+18=-21x | | -2v^2-5v-3=0 | | 1000=x+(x*.8)+(x*.3) | | 3.5q-1.4-5.9q=-3.4q-4.4 | | 1000=x+(x*.8)+(x*.5) | | -5y+4=-6y+5 | | 3x^2-14x=-18 | | 12x+6-3=11x-3 | | -10+3+6=-10 | | -4v^2-13v-3=0 | | -(8y+3)-(-7-4)=-1 | | 0.30(18)+0.05x=0.15(18+x) | | 8-4x+-6x=50 | | 4(2x-1)=2(3x+8) | | 4(3x+12)=2(2x+4) | | 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 | | 6x+35=15x-55 | | 5a-3-4a+3=8 | | (4x^2+3x+5)-(6x^2-8)= | | 6a-2-5a+2=-2 | | X^2+17x=-72 | | -4a+3a-6=-4 | | 9x-19=5x+12 | | 6q-9=4q-19 | | c-5*4=-48 | | 4x+5=24 | | 6x-4=3x+2 |

Equations solver categories